Optimisation of congestion window for TCP adaptation to LEO satellite networks - Abdalla, M. S.; Abdelrahman, A.M.; Ali, B. M. (Institution of Engineering and Technology (IET), 2004)
An optimum mechanism is proposed to adjust congestion window size for enhancing transmission control protocol (TCP) in low earth orbit (LEO) satellite networks. The proposed mechanism adapts between fast throughput recovery and severe congestion avoidance by considering losses in two successive windows. The results indicate that the proposal improves throughput with fairness.